(untitled) (PRÁXIS EM SAÚDE, 2026)
The advancement of digital technologies has significantly transformed the way individuals interact, learn, and process information. In the context of Autism Spectrum Disorder (ASD), these changes become especially relevant, since the virtual environment can act both as a facilitator and as an obstacle to cognitive and social development. This study aims to analyze the impacts of the use of digital technologies on people with ASD, highlighting the positive and negative effects of these tools. The research was conducted through a bibliographic review based on scientific publications published between 2020 and 2025 in the SciELO, PubMed, and PePsic databases. The results indicate that assistive technologies contribute to the improvement of communicative, executive, and social skills, promoting greater autonomy and inclusion. However, excessive screen use and prolonged exposure to digital stimuli may lead to dependency, sensory overload, and harm to mental health. It is concluded that the impact of technology on people with ASD is dual in nature, requiring conscious use guided by qualified professionals. Therefore, the development of interdisciplinary approaches that reconcile technological innovation, inclusion, and cognitive well-being becomes essential.